Excellent service and digital marketing program for the Borobudur Homestay Village Association - Prihatin Dwihantoro; Dwi Susanti; Rayinda Faizah; Sekar Amalia Putri; Nasywa Fildza Nabila (Community Empowerment, 2023)
This community service activity aims to improve the quality of services of the Borobudur Homestay Village community and digital marketing education. The method for this program goes through several stages, namely observation and socialization, training and mentoring, as well as creating a video profile and website for Kampung Homestay Borobudur. The results of this program show an increase in understanding and competence regarding service excellent and digital marketing. Apart from that, a website and company profile have been developed to support the implementation of digital marketing.